Creating a Jazz Discography : the Commerical Recordings of Jo Stafford--the Dorsey Years. - Nelson, Hayley (My University, 2009)
This project assisted in the research and preparation of materials related to building a basic discography of recordings made by jazz artist Jo Stafford (b. 1917) during her prolific professional career as a singer.
Color poster with text and images describing research conducted by Hayley Nelson, advised by Ryan P. Jones.
Keywords: Stafford, Jo--Discography; Big band music--Discography; Jazz vocals--Discography; Jazz singers--Biography; Posters